Multidimensional Assessment of Interoceptive Awareness: Psychometric Properties of the Portuguese Version - Machorrinho, Joana (2020)
Interoceptive awareness involves several mind–body dimensions and can be evaluated by self-report with the Multidimensional Assessment of Interoceptive Awareness (MAIA), which has been translated and validated in several countries and is being used in research and clinical contexts. This study systematically trans- lated the MAIA with six additional items using a focus group and evaluated its psy- chometric properties in a respondent sample of 204 Portuguese university students (52% females; M 1⁄4 21.3, SD 1⁄4 3.9 years). Based on exploratory factor analysis, we refined the tool into a 33-item version and tested it in a separate sample (n 1⁄4 286; 63% females; M1⁄421.3, SD1⁄44.7 years). We then conducted confirmatory factor analysis and examined test–retest reliability and convergent and discriminant validity. We confirmed an acceptable model fit for this Portuguese version (MAIA-P) with 33 items and seven scales; it showed good construct validity and acceptable temporal reliability, The MAIA-P appears to be valuable for assessing self-reported interoceptive awareness in Portuguese healthy adults.